Leader competencies for building psychological safety in hybrid teams: A South African FMCG sector study - Ntando Ngubane; Gloria Mbokota (South African Journal of Business Management)
Purpose: Psychological safety has attracted a fair amount of research in recent years, with most scholars focusing on its importance in driving team performance. Little attention, although, has been given to how leaders build an environment of psychological safety, especially in hybrid work teams in organisations, which have become popular since the coronavirus disease 2019 pandemic. This study aimed to explore how leaders create a psychologically safe environment for hybrid work teams, including the required leader competencies.